Mycobacterium tuberculosis Infection and Innate Responses in a New Model of Lung Alveolar Macrophages - Woo, Minjeong; Wood, Connor; Kwon, Doyoon; Park, Kyu-Ho Paul; Fejer, György; Delorme, Vincent (Frontiers in Immunology, 2018)
Lung alveolar macrophages (AMs) are in the first line of immune defense against respiratory pathogens and play key roles in the pathogenesis of Mycobacterium tuberculosis (Mtb) in humans. Nevertheless, AMs are available only in limited amounts for in vitro studies, which hampers the detailed molecular understanding of host-Mtb interactions in these macrophages. The recent establishment of the self-renewing and primary Max Planck Institute (MPI) cells, functionally very close to lung alveolar macrophages, opens unique opportunities for in vitro studies of host-pathogen interactions in respiratory diseases. Here, we investigated the suitability of MPI cells as a host cell system for Mtb infection. Bacterial, cellular and innate immune features of MPI cells infected with Mtb were characterized. Live bacteria were readily internalized and efficiently replicated in MPI cells, similarly to primary murine macrophages and other cell-lines. MPI cells were also suitable for the determination of anti-tuberculosis drug activity. The primary innate immune response of MPI cells to live Mtb showed significantly higher and earlier induction of the pro-inflammatory cytokines TNFα, IL-6, IL-1α and IL-1β, as compared to stimulation with heat-killed bacteria. MPI cells previously showed a lack of induction of the anti-inflammatory cytokine IL-10 to a wide range of stimuli, including heat-killed Mtb. In contrast, we show here that live Mtb is able to induce significant amounts of IL-10 in MPI cells. Autophagy experiments using LC3B immunostaining, as well as LysoTracker labelling of acidic vacuoles, demonstrated that MPI cells efficiently control killed Mtb by elimination through phagolysosomes. MPI cells were also able to accumulate lipid droplets in their cytoplasm following exposure to lipoproteins. Collectively, this study establishes the MPI cells as a relevant, versatile host cell model for tuberculosis research, allowing a deeper understanding of AMs functions in this pathology.